A non-structural steel slag anti-floating weighted concrete that can replace all aggregates
By using modifiers polymerized by methacrylic acid, 4,4'-diaminodisylene-2,2'-disulfonic acid and n-butyl isobutyrate in concrete, combining cement and steel slag, the problem of structural damage caused by reaction of steel slag with H2O and CO2 in concrete is solved, and the various properties of concrete are significantly improved.
Patent Information
- Application Number
- CN202311223624.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-09-21
Smart Images

Figure BDA0004461518240000081 
Figure BDA0004461518240000091 
Figure BDA0004461518240000092
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of concrete, and in particular to a non-structural steel slag anti-floating weighted concrete capable of replacing all aggregates. Background Art
[0002] Steel slag is an industrial waste discharged during the steelmaking process. Currently, the utilization rate is only 10% to 20%. A large amount of waste slag occupies land and pollutes the environment. Steel slag has a similar strength to natural sand and gravel, has a certain hydraulic gel property, and has a low cost, which makes it suitable for use in construction projects.
[0003] Under the trend of green development, using steel slag as an admixture or aggregate in concrete can not only reduce the land occupation and environmental pollution caused by industrial waste and reduce the material cost of concrete, but also conform to the development direction of reducing, recycling and harmlessly treating solid and hazardous waste.
[0004] The main components of steel slag are CaO, SiO2, Al2O3, Fe2O3, MgO, etc. Since the content of free CaO and MgO in steel slag is relatively high, they can react with H2O and CO2. When steel slag is added to concrete, CaO and MgO easily react with H2O and CO2 that invade the concrete and destroy the structure of the steel slag, thereby reducing the compressive strength of the concrete and limiting the application of steel slag in replacing sand and gravel aggregates in concrete. Summary of the invention
[0005] In view of the fact that CaO and MgO in concrete added with steel slag can react with H2O and CO2 that invade into the concrete to destroy the structure of the steel slag, thereby reducing the compressive strength of the concrete, limiting the application of steel slag in replacing sand and gravel aggregates in concrete, the present application proposes a non-structural steel slag anti-floating counterweight concrete that can replace all aggregates. The concrete is added with a special-effect modifier, which can enable the concrete to maintain good compressive strength for a long time. To this end, the present application specifically adopts the following technical solutions.
[0006] A non-structural steel slag anti-floating weighted concrete capable of replacing all aggregates comprises the following raw materials: cement, fine aggregate steel slag, coarse aggregate steel slag and a modifier. The modifier comprises a polymer obtained by polymerizing methacrylic acid, 4,4'-diaminostilbene-2,2'-disulfonic acid and n-butyl isobutyrate.
[0007] By adopting the above technical scheme, the fine aggregate steel slag and coarse aggregate steel slag completely replace the conventional sand and gravel fine aggregate and coarse aggregate, which can not only reduce the occupation of land and environmental pollution caused by industrial waste steel slag, but also reduce the material cost of concrete, which is in line with the development direction of solid waste reduction, resource utilization and harmlessness. Among them, the polymer polymerized by methacrylic acid, 4,4'-diaminobenzyl-2,2'-disulfonic acid and isobutyl ester is used as a modifier. The modifier has a highly polar hydrophilic group and is doped in cement. It can efficiently bind to the water molecules inside the concrete and attach to the cement particles bound to the water molecules, improve the phenomenon of cement rapid setting and premature hardening, and disperse the cement particles to reduce the sliding resistance between cement particles, thereby improving the workability of fresh concrete and the construction convenience of concrete, and can also reduce the invasion of water molecules into steel slag and protect the steel slag. The modifier also has a thickening effect, which improves the wrapping and floating effect of cement paste on steel slag aggregates, improves the dispersion uniformity of cement and aggregates, and has a strong bonding force with cement and steel slag aggregates, which improves the density of the solidified concrete, thereby significantly improving the impermeability, compressive strength, crack resistance and impact resistance of the concrete after solidification. After the impermeability of concrete is improved, the barrier effect of H2O and CO2 invading concrete is enhanced, and the probability of CaO and MgO in steel slag reacting with H2O and CO2 is reduced, thereby reducing the probability of the steel slag structure being destroyed, and thus also improving the compressive strength of concrete.
[0008] As an improvement of the non-structural steel slag anti-floating weighted concrete that can replace all aggregates, the particle size of the fine aggregate steel slag is 2-5 mm, and the particle size of the coarse aggregate steel slag is 5-10 mm.
[0009] By adopting the above technical solution, since the density of steel slag is greater than that of sand and gravel, relatively speaking, steel slag is easier to settle in cement. If the particle size difference between fine aggregate steel slag and coarse aggregate steel slag is too large, coarse and fine aggregate stratification is likely to occur. Fine aggregate steel slag and coarse aggregate steel slag with the above particle size are dispersed more evenly. The steel slag with the above particle size can be prepared by screening.
[0010] As an improvement of the non-structural steel slag anti-floating weighted concrete that can replace all aggregates, the apparent density of the fine aggregate steel slag is 3.5-3.9 g / cm 3 The apparent density of the coarse aggregate steel slag is 3.0-3.4 g / cm 3 .
[0011] By adopting the above technical solution, the coarse aggregate particles are heavier and the fine aggregate particles are lighter. The apparent density of the coarse aggregate steel slag is slightly smaller than that of the fine aggregate steel slag, which is easier to mix evenly by stirring. Both the coarse and fine aggregates are easily wrapped and floated by the cement paste. The apparent density of the coarse and fine aggregates should not differ too much, otherwise segregation and stratification are likely to occur.
[0012] As an improvement of the non-structural steel slag anti-floating weighted concrete that can replace all aggregates, the anti-floating weighted concrete includes 100 parts of cement, 200-300 parts of fine aggregate steel slag, 450-500 parts of coarse aggregate steel slag and 1-5 parts of modifier, calculated by mass.
[0013] By adopting the above technical solution, cement can be hydrated and the components can be solidified. The modifier is dispersed in the system, which can enhance the floating of the fine aggregate steel slag and the coarse aggregate steel slag, so that each component is evenly dispersed. When using, cement, fine aggregate steel slag and coarse aggregate steel slag can be stirred with water first, and then the modifier can be added to enhance the dispersion effect.
[0014] As an improvement of the non-structural steel slag anti-floating counterweight concrete that can replace all aggregates, the polymer is obtained by the following method: methacrylic acid, 4,4'-diaminostilbene-2,2'-disulfonic acid, n-butyl isobutyrate, a chain transfer agent, an initiator and a solvent are added to a reaction container, heated to 100-150° C., and reacted for 4-8 hours to obtain the polymer.
[0015] By adopting the above technical solution, methacrylic acid, 4,4'-diaminobenzylbenzene-2,2'-disulfonic acid and n-butyl isobutyrate generate free radicals under the action of the initiator to undergo polymerization reaction. The chain transfer agent can transfer the free radicals to change the reaction process and generate more branches. The resulting polymer has a high supporting effect and improves the slump of concrete after adding water and stirring. The polymer also has the effect of improving the compressive strength, impermeability and crack resistance of concrete.
[0016] As an improvement of the non-structural steel slag anti-floating weighted concrete which can replace all aggregates, the initiator is azobisisobutylimidazoline hydrochloride or azobisisobutylamidine hydrochloride.
[0017] By adopting the above technical scheme, azobisisobutylimidazoline hydrochloride and azobisisobutylamidine hydrochloride are basically non-toxic, the azo bond is a weak bond, which is easily broken to form a free radical, and can combine with a double bond to form a new free radical, thereby initiating multiple double bonds to form free radicals and polymerize with each other. The initiator has high polymerization initiation efficiency for methacrylic acid, 4,4'-diaminostilbene-2,2'-disulfonic acid and n-butyl isobutyrate, and high polymerization conversion rate.
[0018] As an improvement of the non-structural steel slag anti-floating weighted concrete capable of replacing all aggregates, the chain transfer agent is dodecanethiol or dithioerythritol.
[0019] By adopting the above technical scheme, during the polymerization reaction process, dodecanethiol and dithioerythritol can combine with free radicals formed by methacrylic acid, 4,4'-diaminostilbene-2,2'-disulfonic acid and n-butyl isobutyrate to transfer the free radicals and form a multi-branched polymer structure.
[0020] As an improvement of the non-structural steel slag anti-floating counterweight concrete that can replace all aggregates, the polymer is prepared, calculated by mass, and the raw materials for preparing the polymer include 60 to 110 parts of methacrylic acid, 300 to 450 parts of 4,4'-diaminostilbene-2,2'-disulfonic acid, 100 to 200 parts of n-butyl isobutyrate, 5 to 20 parts of chain transfer agent and 0.1 to 2 parts of initiator.
[0021] By adopting the above technical solution, the polymerization reaction efficiency is high, the conversion rate is high, and the reaction is relatively complete.
[0022] As an improvement of the non-structural steel slag anti-floating counterweight concrete that can replace all aggregates, the raw materials for preparing the polymer include, calculated by mass, 80 to 90 parts of methacrylic acid, 360 to 380 parts of 4,4'-diaminostilbene-2,2'-disulfonic acid, 135 to 150 parts of n-butyl isobutyrate, 10 to 15 parts of chain transfer agent and 0.8 to 1.2 parts of initiator.
[0023] By adopting the above technical scheme, methacrylic acid, 4,4'-diaminostilbene-2,2'-disulfonic acid, and n-butyl isobutyrate are polymerized at a molar ratio of approximately 1:1:1, with a high polymerization conversion rate and a rich branched structure. The obtained polymer has a strong supporting effect and is added to concrete to improve the workability of the mixed concrete and enhance the compressive strength, impermeability, and crack resistance of the solidified concrete.
[0024] To sum up, the non-structural steel slag anti-floating counterweight concrete that can replace all aggregates in the present application has the following beneficial effects: the fine aggregate steel slag and the coarse aggregate steel slag completely replace the conventional sand and gravel fine aggregate and coarse aggregate, which can not only reduce the land occupation and environmental pollution caused by industrial waste steel slag, but also reduce the material cost of concrete, which is in line with the development direction of reduction, resource utilization and harmlessness of solid waste and hazardous waste.
[0025] The polymer of methacrylic acid, 4,4'-diaminostilbene-2,2'-disulfonic acid and n-butyl isobutyrate is used as a modifier. It has a highly polar hydrophilic group and can be added to cement to efficiently bind to the water molecules inside the concrete and attach to the cement particles bound to the water molecules, thereby improving the phenomenon of premature hardening of cement rapid setting. It also disperses the cement particles and reduces the sliding resistance between the cement particles, thereby improving the workability of the freshly mixed concrete and the convenience of concrete construction. It can also reduce the invasion of water molecules into steel slag, protect the steel slag, and improve the compressive strength of the concrete. The concrete will not easily crack or be damaged when bearing loads.
[0026] After adding water and stirring, the concrete has good fluidity and can be pumped, which enhances the wear resistance, impact resistance and strength of the concrete, increases the surface density of the concrete, reduces dust, and forms a high-density, anti-penetration, anti-floating weighted concrete with good durability. DETAILED DESCRIPTION
[0027] Some embodiments of the non-structural steel slag anti-floating weighted concrete of the present application that can replace all aggregates are described in detail below.
[0028] Example 1
[0029] This embodiment prepares a non-structural steel slag anti-floating weighted concrete that can replace all aggregates. The anti-floating weighted concrete includes the following raw materials by weight: 100 parts of cement, 250 parts of fine aggregate steel slag, 475 parts of coarse aggregate steel slag and 3 parts of modifier.
[0030] The particle size of fine aggregate steel slag is 2-5 mm, and the particle size of coarse aggregate steel slag is 5-10 mm. The apparent density of fine aggregate steel slag is 3.7 g / cm 3 The apparent density of coarse aggregate slag is 3.2g / cm 3 .
[0031] The modifier is a polymer obtained by mutual polymerization of methacrylic acid, 4,4'-diaminobenzylbenzene-2,2'-disulfonic acid, and n-butyl isobutyrate. The polymer is obtained by the following method: 90 parts of methacrylic acid, 360 parts of 4,4'-diaminobenzylbenzene-2,2'-disulfonic acid, 150 parts of n-butyl isobutyrate, 10 parts of chain transfer agent, 1.2 parts of initiator, and 500 parts of water are added to a reactor, heated to 110°C for reflux reaction, reacted for 4 hours, and the water phase was removed to obtain a polymer.
[0032] The chain transfer agent is dodecanethiol, and the initiator is azobisisobutylimidazoline hydrochloride.
[0033] When in use, the above parts by mass of cement, fine aggregate steel slag and coarse aggregate steel slag can be added to 50 parts of water and mixed evenly, and then the modifier can be added and mixed evenly.
[0034] Example 2
[0035] This embodiment adopts a scheme basically the same as that of Embodiment 1 to prepare a non-structural steel slag anti-floating weighted concrete that can replace all aggregates. The only difference is that the anti-floating weighted concrete includes the following raw materials in parts by weight: 100 parts of cement, 200 parts of fine aggregate steel slag, 500 parts of coarse aggregate steel slag and 5 parts of modifier.
[0036] Example 3
[0037] This embodiment adopts a scheme basically the same as that of Embodiment 1 to prepare a non-structural steel slag anti-floating weighted concrete that can replace all aggregates. The only difference is that the anti-floating weighted concrete includes the following raw materials in parts by weight: 100 parts of cement, 300 parts of fine aggregate steel slag, 450 parts of coarse aggregate steel slag and 1 part of modifier.
[0038] Example 4
[0039] This embodiment adopts the same scheme as that of embodiment 1 to prepare a non-structural steel slag anti-floating weighted concrete that can replace all aggregates. The only difference is that the apparent density of the fine aggregate steel slag is 3.9 g / cm 3 The apparent density of coarse aggregate slag is 3.0g / cm 3 .
[0040] Example 5
[0041] This embodiment adopts the same scheme as that of embodiment 1 to prepare a non-structural steel slag anti-floating weighted concrete that can replace all aggregates. The only difference is that the apparent density of the fine aggregate steel slag is 3.5g / cm 3 The apparent density of coarse aggregate slag is 3.4g / cm 3 .
[0042] Example 6
[0043] This embodiment adopts a scheme basically the same as that of Embodiment 1 to prepare a non-structural steel slag anti-floating counterweight concrete that can replace all aggregates. The only difference is that the raw material ratio for preparing the polymer is different: the polymer raw materials of this embodiment include 110 parts of methacrylic acid, 300 parts of 4,4'-diaminostilbene-2,2'-disulfonic acid, 100 parts of n-butyl isobutyrate, 5 parts of chain transfer agent, 0.1 parts of initiator and 500 parts of water.
[0044] Example 7
[0045] This embodiment adopts a scheme basically the same as that of Embodiment 1 to prepare a non-structural steel slag anti-floating counterweight concrete that can replace all aggregates. The only difference is that the raw material ratio for preparing the polymer is different: the polymer raw materials of this embodiment include 60 parts of methacrylic acid, 450 parts of 4,4'-diaminobis(phenylene glycol)-2,2'-disulfonic acid, 200 parts of n-butyl isobutyrate, 20 parts of chain transfer agent, 2 parts of initiator and 500 parts of water.
[0046] Example 8
[0047] This embodiment adopts a scheme basically the same as that of Embodiment 1 to prepare a non-structural steel slag anti-floating counterweight concrete that can replace all aggregates. The only difference is that the raw material ratio for preparing the polymer is different: the polymer raw materials of this embodiment include 80 parts of methacrylic acid, 380 parts of 4,4'-diaminostilbene-2,2'-disulfonic acid, 135 parts of n-butyl isobutyrate, 15 parts of chain transfer agent and 0.8 parts of initiator.
[0048] The raw materials for preparing the polymer include 60-110 parts of methacrylic acid, 300-450 parts of 4,4'-diaminostilbene-2,2'-disulfonic acid, 100-200 parts of n-butyl isobutyrate, 5-20 parts of chain transfer agent and 0.1-2 parts of initiator.
[0049] Example 9
[0050] This embodiment adopts a scheme basically the same as that of Embodiment 1 to prepare a non-structural steel slag anti-floating counterweight concrete that can replace all aggregates. The only difference is that the raw material ratio for preparing the polymer is different: the polymer raw materials of this embodiment include 86 parts of methacrylic acid, 370 parts of 4,4'-diaminobis(phenylene glycol)-2,2'-disulfonic acid, 142 parts of n-butyl isobutyrate, 10 parts of chain transfer agent and 1.2 parts of initiator.
[0051] Example 10
[0052] This embodiment adopts a scheme that is basically the same as that of Embodiment 1 to prepare a non-structural steel slag anti-floating weighted concrete that can replace all aggregates. The only difference is that the chain transfer agent in this embodiment is dithioerythritol.
[0053] Embodiment 11
[0054] This embodiment adopts a scheme that is basically the same as that of Embodiment 1 to prepare a non-structural steel slag anti-floating weighted concrete that can replace all aggregates. The only difference is that the initiator of this embodiment is azobisisobutyramidine hydrochloride.
[0055] Comparative Example 1
[0056] This comparative example adopts the same scheme as Example 1 to prepare a non-structural steel slag anti-floating weighted concrete that can replace all aggregates. The only difference is that the particle size of the fine aggregate steel slag is 0.2-1 mm, and the particle size of the coarse aggregate steel slag is 15-25 mm. The apparent density of the fine aggregate steel slag is 3.9 g / cm 3 The apparent density of coarse aggregate slag is 3.0g / cm 3 .
[0057] Comparative Example 2
[0058] This comparative example adopts a scheme basically the same as that of Example 1 to prepare a non-structural steel slag anti-floating counterweight concrete that can replace all aggregates. The only difference is that the concrete of this comparative example does not contain a modifier. Specifically, the concrete of this comparative example includes 100 parts of cement, 250 parts of fine aggregate steel slag, and 475 parts of coarse aggregate steel slag.
[0059] Comparative Example 3
[0060] This comparative example adopts a scheme that is basically the same as that of Example 1 to prepare a non-structural steel slag anti-floating counterweight concrete that can replace all aggregates. The only difference is that the raw material ratio for preparing the polymer is different. The raw materials for preparing the polymer in this comparative example include 30 parts of methacrylic acid, 500 parts of 4,4'-diaminobenzyl-2,2'-disulfonic acid, 300 parts of n-butyl isobutyrate, 10 parts of chain transfer agent and 1.2 parts of initiator. The chain transfer agent is also dodecanethiol, and the initiator is also azobisisobutylimidazoline hydrochloride.
[0061] Comparative Example 4
[0062] This comparative example adopts a scheme that is basically the same as that of Example 1 to prepare a non-structural steel slag anti-floating counterweight concrete that can replace all aggregates. The only difference is that the raw material ratio for preparing the polymer is different. The raw materials for preparing the polymer in this comparative example include 30 parts of methacrylic acid, 200 parts of 4,4'-diaminobenzyl-2,2'-disulfonic acid, 300 parts of n-butyl isobutyrate, 10 parts of chain transfer agent and 1.2 parts of initiator. The chain transfer agent is also dodecanethiol, and the initiator is also azobisisobutylimidazoline hydrochloride.
[0063] Comparative Example 5
[0064] This comparative example adopts a scheme that is basically the same as that of Example 1 to prepare a non-structural steel slag anti-floating counterweight concrete that can replace all aggregates. The only difference is that the raw material ratio for preparing the polymer is different. The raw materials for preparing the polymer in this comparative example include 150 parts of methacrylic acid, 200 parts of 4,4'-diaminobenzyl-2,2'-disulfonic acid, 300 parts of n-butyl isobutyrate, 10 parts of chain transfer agent and 1.2 parts of initiator. The chain transfer agent is also dodecanethiol, and the initiator is also azobisisobutylimidazoline hydrochloride.
[0065] Comparative Example 6
[0066] This comparative example adopts a scheme that is basically the same as that of Example 1 to prepare a non-structural steel slag anti-floating counterweight concrete that can replace all aggregates. The only difference is that the raw material ratio for preparing the polymer is different. The raw materials for preparing the polymer in this comparative example include 150 parts of methacrylic acid, 200 parts of 4,4'-diaminobenzyl-2,2'-disulfonic acid, 50 parts of n-butyl isobutyrate, 10 parts of chain transfer agent and 1.2 parts of initiator. The chain transfer agent is also dodecanethiol, and the initiator is also azobisisobutylimidazoline hydrochloride.
[0067] Comparative Example 7
[0068] This comparative example adopts a scheme basically the same as that of Example 1 to prepare a non-structural steel slag anti-floating counterweight concrete that can replace all aggregates. The only difference is that the raw materials for preparing the polymer do not include methacrylic acid, and the amounts of 4,4'-diaminobis(phenylethylene)-2,2'-disulfonic acid and n-butyl isobutyrate are increased by 45 parts respectively.
[0069] Specifically, the raw materials for preparing the polymer in this comparative example include 405 parts of 4,4'-diaminobenzylbenzene-2,2'-disulfonic acid, 195 parts of n-butyl isobutyrate, 10 parts of chain transfer agent and 1.2 parts of initiator. The chain transfer agent is also dodecanethiol, and the initiator is also azobisisobutylimidazoline hydrochloride.
[0070] Comparative Example 8
[0071] This comparative example adopts a scheme basically the same as that of Example 1 to prepare a non-structural steel slag anti-floating counterweight concrete that can replace all aggregates. The only difference is that the raw materials for preparing the polymer do not include 4,4'-diaminostilbene-2,2'-disulfonic acid, and the amounts of methacrylic acid and n-butyl isobutyrate are increased by 180 parts respectively.
[0072] Specifically, the raw materials for preparing the polymer in this comparative example include 270 parts of methacrylic acid, 330 parts of n-butyl isobutyrate, 10 parts of chain transfer agent and 1.2 parts of initiator. The chain transfer agent is also dodecanethiol, and the initiator is also azobisisobutylimidazoline hydrochloride.
[0073] Comparative Example 9
[0074] This comparative example adopts a scheme basically the same as that of Example 1 to prepare a non-structural steel slag anti-floating counterweight concrete that can replace all aggregates. The only difference is that the raw materials for preparing the polymer do not include n-butyl isobutyrate, and the amounts of methacrylic acid and 4,4'-diaminostilbene-2,2'-disulfonic acid are increased by 75 parts each.
[0075] Specifically, the raw materials for preparing the polymer in this comparative example include 165 parts of methacrylic acid, 435 parts of 4,4'-diaminobenzylbenzene-2,2'-disulfonic acid, 10 parts of chain transfer agent and 1.2 parts of initiator. The chain transfer agent is also dodecanethiol, and the initiator is also azobisisobutylimidazoline hydrochloride.
[0076] Test Example 1
[0077] 50 parts of water were added to the concrete prepared in Examples 1-11 and Comparative Examples 1-9, and the mixture was stirred and evenly mixed to prepare various test samples, and the compressive strength, apparent density, slump, crack resistance, impermeability grade, chloride ion migration coefficient, and initial crack impact times of each sample were tested respectively. The test methods of each test item and the reference standards for the test results are as follows.
[0078] Compressive strength: The test method refers to "GB / T 50081-2019 Standard for Test Methods for Physical and Mechanical Properties of Concrete".
[0079] Apparent density: The detection method refers to GB / T 50080-2016 Standard for Test Methods of Performance of Ordinary Concrete Mixtures.
[0080] Slump: The detection method refers to "GB / T 50080-2016 Standard for Test Methods of Performance of Ordinary Concrete Mixtures".
[0081] Anti-cracking performance: The detection method refers to "GB / T 50082-2009 Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete".
[0082] Waterproof grade: The waterproof grade of concrete is tested by the step-by-step pressure method in accordance with 6.2 of GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete".
[0083] Chloride ion migration coefficient: in accordance with 7.1 rapid chloride ion migration coefficient method in GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete".
[0084] Number of initial crack impacts: refer to the drop hammer method in CECS13-2009 "Fiber Concrete Test Method Standard".
[0085] The test results of the above test items for the concrete prepared in Examples 1-11 and Comparative Examples 1-9 are shown in Tables 1 and 2 below.
[0086] Table 1 Concrete performance test results prepared by Examples 1-11 and Comparative Examples 1-9
[0087]
[0088]
[0089] Table 2 Concrete performance test results prepared by Examples 1-11 and Comparative Examples 1-9
[0090]
[0091]
[0092] It can be seen from the results in Table 1 and Table 2 that the compressive strength, apparent density, slump, crack resistance, impermeability grade, resistance to chloride ion penetration, and initial crack impact times of the samples of Examples 1-11 are stronger than those of the samples of Comparative Examples 1-9 as a whole, indicating that the scheme of Examples 1-11 can achieve better concrete performance effects.
[0093] Compared with Example 1, Examples 6 and 7 significantly adjusted the raw material ratio for preparing the polymer, and their compressive strength, slump, crack resistance, impermeability grade, resistance to chloride ion penetration, and initial crack impact times were all reduced.
[0094] Compared with Example 1, Example 8 slightly adjusted the raw material ratio for preparing the polymer, and its compressive strength, slump, crack resistance, resistance to chloride ion penetration, and initial crack impact number are equivalent to those of the sample in Example 1.
[0095] Compared with Example 1, Example 9 slightly adjusted the raw material ratio for preparing the polymer, and its compressive strength, slump, crack resistance, resistance to chloride ion penetration, and initial crack impact times were all slightly improved compared with Example 1.
[0096] In Example 10, compared with Example 1, the chain transfer agent is changed from dodecanethiol to dithioerythritol, and its compressive strength, slump, crack resistance, resistance to chloride ion penetration, and initial crack impact times are slightly improved compared with those of Example 1.
[0097] Compared with Example 1, the initiator of Example 11 is changed from azobisisobutylimidazoline hydrochloride to azobisisobutylamidine hydrochloride, and its compressive strength, slump, crack resistance, resistance to chloride ion penetration, and initial crack impact number are equivalent to those of the sample in Example 1.
[0098] Compared with Example 1, Comparative Example 1 used fine aggregate steel slag with a smaller particle size and coarse aggregate steel slag with a larger particle size. The particle size of the fine aggregate steel slag was 0.2-1 mm, and the particle size of the coarse aggregate steel slag was 15-25 mm. The compressive strength, slump, crack resistance, impermeability grade, resistance to chloride ion penetration, and number of initial crack impacts were all reduced. This is mainly because the particle sizes of the fine aggregate steel slag and the coarse aggregate steel slag are too different, which easily leads to sedimentation and uneven mixing, affecting the performance of the concrete.
[0099] Compared with Example 1, in Comparative Example 2, no modifier was added, and its compressive strength, slump, crack resistance, impermeability grade, resistance to chloride ion penetration, and initial crack impact times were all significantly reduced.
[0100] Compared with Example 1, in Comparative Example 3, the addition ratio of methacrylic acid is too small, while the addition ratio of 4,4'-diaminostilbene-2,2'-disulfonic acid and n-butyl isobutyrate is too large, resulting in a significant decrease in its compressive strength, slump, crack resistance, impermeability grade, resistance to chloride ion penetration, and number of initial crack impacts.
[0101] Compared with Example 1, the addition ratio of methacrylic acid and 4,4'-diaminostilbene-2,2'-disulfonic acid is too small, while the addition ratio of n-butyl isobutyrate is too large, resulting in a significant decrease in its compressive strength, slump, crack resistance, impermeability grade, resistance to chloride ion penetration, and number of initial crack impacts.
[0102] Compared with Example 1, in Comparative Example 5, the addition ratio of methacrylic acid and n-butyl isobutyrate is too large, while the addition ratio of 4,4'-diaminostilbene-2,2'-disulfonic acid is too small, resulting in a significant decrease in its compressive strength, slump, crack resistance, impermeability grade, resistance to chloride ion penetration, and number of initial crack impacts.
[0103] Compared with Example 1, the proportion of methacrylic acid added in Comparative Example 6 is too large, while the proportion of 4,4'-diaminostilbene-2,2'-disulfonic acid and n-butyl isobutyrate added is too small, resulting in a significant decrease in its compressive strength, slump, crack resistance, impermeability grade, resistance to chloride ion penetration, and number of initial crack impacts.
[0104] Compared with Example 1, in Comparative Example 7, the raw materials for preparing the polymer do not include methacrylic acid, and the amount of original methacrylic acid is supplemented with 4,4'-diaminostilbene-2,2'-disulfonic acid and n-butyl isobutyrate. The compressive strength, slump, crack resistance, impermeability grade, resistance to chloride ion penetration, and number of initial crack impacts of the concrete are significantly reduced.
[0105] Compared with Example 1, Comparative Example 8, the raw materials for preparing the polymer do not include 4,4'-diaminostilbene-2,2'-disulfonic acid, and methacrylic acid and n-butyl isobutyrate are used to supplement the original 4,4'-diaminostilbene-2,2'-disulfonic acid. The compressive strength, slump, crack resistance, impermeability grade, resistance to chloride ion penetration, and the number of initial crack impacts of the concrete are significantly reduced.
[0106] Compared with Example 1, Comparative Example 9, in which the raw materials for preparing the polymer do not include n-butyl isobutyrate, and methacrylic acid and 4,4'-diaminostilbene-2,2'-disulfonic acid are used to supplement the amount of n-butyl isobutyrate, the compressive strength, slump, crack resistance, impermeability grade, resistance to chloride ion penetration, and number of initial crack impacts of the concrete are significantly reduced.
[0107] The concrete prepared in Example 1-11 has an initial setting time of about 3 hours, a final setting time of about 6 hours, a compressive strength of 30-36 MPa in 7 days, a compressive strength of 55-61 MPa in 28 days, and a compressive strength of 69-78 MPa in 60 days. The initial slump is 220-231 mm, and the slump decreases by 6-18 mm after 40 minutes. The concrete has good workability and meets the requirements of pumping construction. Its compressive strength, workability, crack resistance, impermeability, and impact resistance are all better than the scheme without adding a modifier in Example 2. The modifier in Example 1-11 is a two-layer polymerized methacrylic acid, 4,4'-diaminobenzene-2,2'-disulfonic acid, and n-butyl isobutyrate. It has a strong polar hydrophilic group, a large number of branched structures, and a steric hindrance effect. It can be adsorbed on the surface of cement particles, and a steric hindrance effect is generated between cement particles, so that the slump of the concrete is well maintained.
[0108] The anti-floating weighted concrete prepared in Examples 1-11 has good anti-seepage performance and can effectively prevent water and moisture from penetrating into the interior of the concrete. The concrete is not easy to age and corrode, and is suitable for use in basements or underwater environments.
[0109] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. All equivalent changes made according to the principles of the present application should fall within the protection scope of the present application.
Claims
1. A non-structural steel slag anti-floating weighted concrete that can replace all aggregates, characterized in that: Contains the following raw materials: cement, fine aggregate steel slag, coarse aggregate steel slag and modifier; The modifier includes a polymer obtained by polymerizing methacrylic acid, 4,4'-diaminostilbene-2,2'-disulfonic acid and n-butyl isobutyrate; The polymer is obtained by the following method: adding methacrylic acid, 4,4'-diaminostilbene-2,2'-disulfonic acid, n-butyl isobutyrate, a chain transfer agent, an initiator and a solvent into a reaction container, heating to 100-150° C., reacting for 4-8 hours, and obtaining the polymer; The raw materials for preparing the polymer include 60-110 parts of methacrylic acid, 300-450 parts of 4,4'-diaminostilbene-2,2'-disulfonic acid, 100-200 parts of n-butyl isobutyrate, 5-20 parts of a chain transfer agent and 0.1-2 parts of an initiator.
2. The non-structural steel slag anti-floating weighted concrete capable of replacing all aggregates according to claim 1 is characterized in that: The particle size of the fine aggregate steel slag is 2-5 mm, and the particle size of the coarse aggregate steel slag is 5-10 mm.
3. The non-structural steel slag anti-floating weighted concrete capable of replacing all aggregates according to claim 1 or 2, characterized in that: The apparent density of the fine aggregate steel slag is 3.5-3.9 g / cm 3 The apparent density of the coarse aggregate steel slag is 3.0-3.4 g / cm 3 .
4. The non-structural steel slag anti-floating weighted concrete capable of replacing all aggregates according to claim 1, characterized in that: Calculated by weight, the anti-floating weighted concrete includes 100 parts of cement, 200-300 parts of fine aggregate steel slag, 450-500 parts of coarse aggregate steel slag and 1-5 parts of modifier.
5. The non-structural steel slag anti-floating weighted concrete capable of replacing all aggregates according to claim 1, characterized in that: The initiator is azobisisobutylimidazoline hydrochloride or azobisisobutylamidine hydrochloride.
6. The non-structural steel slag anti-floating weighted concrete capable of replacing all aggregates according to claim 1, characterized in that: The chain transfer agent is dodecanethiol or dithioerythritol.
7. The non-structural steel slag anti-floating weighted concrete capable of replacing all aggregates according to claim 1, characterized in that: Calculated by weight, the raw materials for preparing the polymer include 80-90 parts of methacrylic acid, 360-380 parts of 4,4'-diaminostilbene-2,2'-disulfonic acid, 135-150 parts of n-butyl isobutyrate, 10-15 parts of a chain transfer agent and 0.8-1.2 parts of an initiator.
Citation Information
Patent Citations
Pumpable counterweight concrete
CN107902997A
Aqueous wetting dispersant preparation method and aqueous wetting dispersant and applications thereof
CN110818845A
Cited By
Green long-life double-layer cement concrete pavement and construction method
CN122610418A